Therapeutic drug Monitoring of Darunavir/Ritonavir in Pregnancy. Issue 3 (April 2019) - Murtagh, Ross; Else, Laura J; Kuan, Kenneth BK; Khoo, Saye H; Jackson, Valerie; Patel, Anjali; Lawler, Marguerite; McDonald, Grainne; Le Blanc, David; Avramovic, Gordana; Redmond, Niamh; Lambert, John S
Background: Physiological changes during pregnancy can have a significant impact on antiretroviral pharmacokinetics (PK), which may result in reduced drug efficacy. Here we describe the PK of darunavir/ritonavir (DRV/r) 800/100 once daily in a cohort of pregnant women undergoing routine therapeutic drug monitoring (TDM) as well as transplacental passage of DRV by measuring and comparing cord blood and maternal blood samples at delivery. Methods: Pregnant HIV-positive women received DRV/r as part of routine pre-natal care. Demographic and clinical data were collected. DRV plasma concentrations [DRV] were determined in the first (T1), second (T2) and third (T3) trimester and at postpartum (PP). The target concentration was 550 ng/ml. Where possible, paired maternal and cord blood samples were taken at delivery. Results: A total of 33 women were enrolled. Samples were taken 14–20 h post-dose and measured concentrations were extrapolated to 24 h post-dose. At the time nearest to delivery, all but four had undetectable plasma viral loads (pVL). [DRV] were determined in 1 (T1); 14 (T2); 32 (T3) and 29 (PP). 1 sample was <550 ng/ml at T2, 6 at T3 and 3 at PP. [DRV] were significantly lower at T2/T3 relative to PP. Conclusions: [DRV] in T2 and T3 were 36–55% when compared with PP. However, DRV PK in pregnancy were not associated with a lack of virological suppression at delivery as of the 33 patients enrolled in this study, 31 had no HIV transmission from mother to child. Data regarding two candidates were not available as they delivered in a separate health-care facility.